Pengaruh Perilaku Konsumen dan Desain Produk terhadap Keputusan Pembelian Produk Imitasi Jenis Fashion (Sepatu Vans) di Kalangan Mahasiswa FEB Universitas Muhammadiyah Metro - marhaban, irfan; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2021)
Along with the rapid economic development, the various needs for a type of product are increasing and varying in the market. Consumers will judge every side of the product that is needed. One of the product categories currently circulating in the student environment is a fashion imitation product. The types of fashion products that are often used to support everyday appearances and don't forget to use them by students are the Vans brand shoes.Researchers use this type of quantitative research or verification research. In this study, the population was FEB students of Muhammadiyah Metro University. The sampling technique used accidental sampling with a sample size of 100 people. The data collection technique used a questionnaire with a Likert scaleThe results showed that: (1) there was a positive influence on consumer behavior on purchasing decisions for imitation products, vans shoe fashion (2) there was a positive effect on product design on purchasing decisions for vans shoe fashion imitation products (3) there was an influence on consumer behavior and product design. , jointly on the purchasing decision.